1991
DOI: 10.1093/ptj/71.4.283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Exercise Program on Sick Leave Due to Back Pain

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(74 citation statements)
references
References 2 publications
2
68
1
3
Order By: Relevance
“…14 Lahad et al 15 identified several randomized, controlled trials of education and exercise programs in the workplace. [16][17][18][19][20][21] Programs including exercise reduced back pain and the number of sick days, but no program reduced injury rates. The generalizability of these studies was limited by the small samples and a focus on volunteers or subjects with a history of back problems.…”
Section: Methodsmentioning
confidence: 99%
“…14 Lahad et al 15 identified several randomized, controlled trials of education and exercise programs in the workplace. [16][17][18][19][20][21] Programs including exercise reduced back pain and the number of sick days, but no program reduced injury rates. The generalizability of these studies was limited by the small samples and a focus on volunteers or subjects with a history of back problems.…”
Section: Methodsmentioning
confidence: 99%
“…The results show that regular back exercise reduces back pain and improves the ability to function for subjects with chronic LBR Back exercise may reduce the back pain episode and thus the period of sickness absence for patients with acute LBP and partially decrease the risk of developing chronic LBP in the future [12,14,[17][18][19][20]. The favourable effect of back exercise may be due to a combination of physical and psychological factors [1,21].…”
Section: Introductionmentioning
confidence: 99%
“…A review of exercises for the prevention of LBP recurrence (12) identified only four studies evaluating so-called post-treatment interventions, delivered after the resolution of an LBP episode in order to prevent new episodes. Based on two studies, there was very low quality evidence that post-treatment exercises could reduce the number of days on sick leave at mid-term follow-up (13,14). This positive effect was lacking at long-term follow-up (13), and new trials were deemed necessary to figure out which strategies could prevent LBP recurrence and related work disability in the long term (12).…”
mentioning
confidence: 99%